Effect of Possible Osteoporosis on Parenchymal-Type Hemorrhagic Transformation in Patients with Cardioembolic Stroke - Won, Yu-Deok (J Clin Med, 2021)
Background: hemorrhagic transformation (HT) is a frequent complication of ischemic stroke, and parenchymal hematoma (PH)-type HT has been shown to correlate with symptomatic deterioration. Because both bone and vascular smooth muscle cells are composed of type 1 collagen, we hypothesized that the integrity of blood vessels around the infarction area might be more damaged in osteoporotic conditions after a cardioembolic stroke. Methods: we measured frontal skull Hounsfield unit (HU) values on brain CT images from cardioembolic stroke patients. We conducted a receiver operating characteristic curve analysis in a large sample registry to identify the optimal HU threshold for predicting osteopenia and osteoporosis. Hazard ratios were estimated using a Cox regression analysis to identify whether osteoporotic conditions were an independent predictor of PH-type HT in patients with cardioembolic stroke. Results: altogether, 600 consecutive patients (>18 years old) with cardioembolic stroke were enrolled over a 12-year period at our hospital. The infarction volume and hypothetical osteoporosis were independent predictive factors for PH-type HT development in patients with cardioembolic stroke. In the male group, hypothetical osteoporosis was an independent predictor for PH-type HT development after cardioembolic stroke (hazard ratio, 4.12; 95% confidence interval, 1.40–12.10; p = 0.010). Conclusions: our study suggests an association between possible osteoporosis and the development of PH-type HT in patients with cardioembolic stroke. Our findings could help to predict PH-type HT by providing a convenient method for measuring the HU value using brain CT images.